Effect of Leg Exercise on the Lower Limb Circulation of Patients with Diabetes Mellitus: A Systematic Review - Ida Trisnawati; I Ketut Sudiana; Supriyanto Supriyanto (Universitas Airlangga, 2020)
Introduction: Hyperglycemia is one of the typical symptoms of patients with diabetes mellitus. This systematic review aims to systematically review the research evidence related to the effects of leg exercise on increasing the value of the ankle-brachial index in patients with diabetes mellitus.Methods: This study used a systematic review with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) approach. We identified 85 articles from Scopus, 34 from Pubmed and 401 from ProQuest. The keywords used in the search were